Peran Nano Biokarbon Aktif Dari Kulit Pinang Terhadap Karakteristik Pembakaran Droplet Minyak Biji Bunga Matahari - Harsanta, Bagus E.; Riupassa, Helen; Nanlohy, Hendry Y. (Infotekmesin, 2025)
Continuous exploitation of fossil fuels causes scarcity, so appropriate solutions and policies are needed. One of these solutions is to utilize vegetable oil, and one of them comes from sunflower seed oil, which contains 17% oleic fatty acid and around 73% linoleic. However, its high viscosity, making it difficult to burn, hampers its use as an alternative fuel. Therefore, efforts are made to reduce its viscosity. One of these efforts is to add a catalyst in the form of active nano bio carbons derived from areca nut skin. Droplet combustion is chosen to increase the contact area between air and fuel so that the reactivity of fuel molecules increases. The study's results showed that the quality of fuel produced from a mixture of sunflower seed oil and active nano biocarbon from areca nut skin was improved. It was found that a concentration of 1 ppm was the best compared to other concentrations (2 and 3 ppm). It can be seen that it was able to reduce the viscosity of sunflower seed oil to 11.16 cSt, reduce the flash point at 138Â°C, and can increase the droplet combustion rate by around 2.05 seconds.